The role of teledentistry in oral surgery during the COVID-19 pandemic - Afnan Ibraheim; Arwa Sanalla; Josiah Eyeson (Elsevier, 2021)
Objectives: Evaluation of patient experience of teledentistry during the coronavirus pandemic and establishing the clinical effectiveness of teleclinics in this context. Methods: 103 follow-up patients who had a telephone review during the pandemic were included. A five-item, five-point Likert-scale telephone survey was used to gauge patient experience. In addition, retrospective analysis of these patients' electronic records was done to establish effectiveness of the telephone review. Patients' responses and data collected were then analysed. Results: In terms of patient experience of their telephone review, 70% found the telephone review was useful, 77% felt their concerns were addressed, 99% felt it was easy to access and time saving, 94% felt they could discuss their healthcare matters on the phone, and 62% felt they preferred telephone reviews rather than face-to-face reviews for their follow-up appointments.When analysing effectiveness of the telephone review, 62% of patients could be discharged following the teleconsultation, suggesting it was sufficient alone to complete these patients' care. All relevant clinical information was present for 98% of the teleconsultations to proceed. Results showed teledentistry was particularly effective for follow-up patients requiring a post-operative review or finalisation of treatment plans. Conclusion: Patients had a positive experience of telephone clinics for the provision of their routine follow-up care. In addition, teledentistry is shown to be a means of increasing capacity for face-to-face reviews, in turn reducing waiting times and further improving patient experience. Appropriate case selection for teledentistry is essential. Teledentistry is an efficient and effective tool for patient care when used suitably and can have an important role in routine patient care beyond the pandemic.